IMPLEMENTASI METODE DISKUSI KELOMPOK PADA MATA KULIAH MENEJEMEN MADRASAH DI IAIN SAS BANGKA BELITUNG - Firdian, Firdian; Santosa, Sedya (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
This study aims to determine the implementation of the discussion method in madrasah management courses. This research method is qualitative research, the subject of this research in lecturer and college student, the object of this research is in the form of a discussion method implemention model in optimizing learning, data collection teachniques with observation methods, interviews, and documentation. The results of this study show that the discussion method in Madrasah Management learning, class D student, IAIN SAS Bangka Belitung, has shown that the implementation of the discussions method has been going well, from the student preparation process, in understanding learning topics, and something interesting problem, and student responses are in accordance with the discussion material, have the skills to ask and answer, and have been active in discussions.